Analysis Of The Relationship Between Corporate Sutainability Disclosure and Esg Ratings By Msci, Sustainalytics, And Cdp (A Study Of The Sus-tainability Report Of Pt Pertamina (Persero)) - Yurisca, Winda (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This research aims to analyze ESG ratings by MSCI, Sustainalytics, and CDP based on differences in methodology, data sources, assessment focus, and the relationship between PT Pertamina (Persero)'s sustainability report disclosure and its ESG ratings. This research employs a descriptive qualitative method, utilizing data from the ESG Risk Ratings Methodology Report and PT Pertamina's Sustainability Report. The results indicate variations in ESG assessment methodology and focus. MSCI applies a scoring system with additional qualitative assessments, Sustainalytics emphasizes exposure and management, while CDP focuses on management and A-List criteria. Data sources also differ: MSCI uses shareholder meeting documents, Sustainalytics relies on peer reviews and financial filings, and CDP utilizes emission reports, supply chain data, and stakeholder engagement. The publication of PT Pertamina (Persero)’s sustainability report influences its ESG ratings. Based on the 2023 report, Pertamina received a BB/Average score (MSCI), 20.7/Medium Risk (Sustainalytics), and B- (CDP), indicating the need for improvements in ESG aspects and climate change management.